Sampling for household-based surveys of child labour - Verma, Vijay; International Labour Office; International Programme on the Elimination of Child Labour (Geneva : ILO, 2008)
This manual presents a wide range of sampling techniques for household-based child labour surveys with a particular emphasis on sampling design and selection procedures. It is meant to assist survey professionals in statistical offices, universities and research organizations. Many of the concepts and approaches introduced by the Manual are illustrated with examples from SIMPOC child labour surveys conducted in all major world regions.
Introduction: uses and limitations of household-based surveys of child labour -- Choosing an appropriate survey structure -- Sampling for a typical population-based survey -- Child labour survey (CLS): linked sample of reduced size -- Labouring children survey (LCS) -- An illustration of sample design and selection procedures -- Estimation from sample data.
References.
eBooks on EBSCOhost
Keywords: Child labor -- Research; Social surveys; Enfants -- Travail -- Recherche; Enquêtes sociales; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Social surveys; child labour; survey; sample; statistical method; developing countries; travail des enfants; enquête.; échantillon.; méthode statistique; pays en développement.; trabajo infantil; encuesta; muestra; método estadístico.; países en desarrollo; Guide; ILO pub; Guide; Pub OIT; Guía.; Pub OIT